Biosensing bacterial 16S rDNA by microchip electrophoresis combined with a CRISPR system based on real-time crRNA/Cas12a formation. Issue 34 (10th August 2022) - Luo, Feifei; Geng, Xing; Li, Zhi; Dai, Ge; Chu, Zhaohui; He, Pingang; Zhang, Fan; Wang, Qingjiang
Abstract : Real-time crRNA/Cas12a formation derived CRISPR system for bacterial sensing. Abstract : The accurate, simple and sensitive detection of bacterial infections at the early stage is highly valuable in preventing the spread of disease. Recently, CRISPR–Cas12a enzyme-derived nucleic acid detection methods have emerged along with the discovery of the indiscriminate single-stranded DNA (ssDNA) cleavage activity of Cas12a. These nucleic acid detection methods are made effective and sensitive by combining them with isothermal amplification technologies. However, most of the proposed CRISPR–Cas12a strategies involve Cas–crRNA complexes in the preassembled mode, which result in inevitable nonspecific background signals. Besides, the signal ssDNA used in these strategies needs tedious pre-labeling of the signal molecules. Herein, a post-assembly CRISPR–Cas12a method has been proposed based on target-induced transcription amplification and real-time crRNA generation for bacterial 16S rDNA biosensing. This strategy is label-free through the combination of microchip electrophoresis (MCE) detection. In addition, this method eliminates the need for a protospacer adjacent motif (PAM) on the target sequences, and has the potential to be an effective and simple method for nucleic acid detection and infectious disease diagnosis.